Researching forced labour in the global economy methodological challenges and advances - LeBaron, Genevieve (Oxford The British Academy by Oxford University Press, 2018)
"By most accounts, forced labour, human trafficking, and modern slavery are thriving in the global economy. Recent media reports -- including the discovery of widespread trafficking in Thailand's shrimp industry, forced labour in global tea and cocoa supply chains, and the devastating deaths of workers constructing stadiums for Qatar's World Cup-- have brought once hidden exploitation into the mainstream spotlight. As public concern about forced labour has escalated, governments around the world have begun to enact legislation to combat it in global production. Yet, in spite of soaring media and policy attention, reliable research on the business of forced labour remains difficult to come by. Forced labour is notoriously challenging to investigate, given that it is illegal, and powerful corporations and governments are reluctant to grant academics access to their workers and supply chains. Given the risk associated with researching the business of forced labour, until very recently, few scholars even attempted to collect hard or systematic data. Instead, academics have often had little choice but to rely on poor quality second-hand data, frequently generated by activists and businesses with vested interests in portraying the problem in a certain light. As a result, the evidence base on contemporary forced labour is both dangerously thin and riddled with bias. Researching Forced Labour in the Global Economy gathers an interdisciplinary group of leading scholars to tackle this problem. It provides the first, comprehensive, scholarly account of forced labour's role in the contemporary global economy and reflections on the methodologies used to generate this research" -- Provided by publisher.
g1. Understanding the global business of forced labour : an introduction Genevieve LeBaron -- Part I. Surveying the gaps : analytical and methodological challenges. 2. Methodological challenges in the business of forced labour Genevieve LeBaron and Andrew Crane -- 3. The politics of numbers : beyond methodological challenges in research on forced labour Nicola Phillips -- 4. Evaluating the political effects of anti-slavery and anti-trafficking activism Joel Quirk -- 5. What is forced labour? A practical guide for humanities and social science research Jean Allain -- 6. Confronting bias in NGO research on modern slavery Samuel Okyere -- Part II. Frontiers of forced labour research and methods. 7. Why (and how) we need to talk to 'the victims' Neil Howard -- 8. Researching unfree student labour in Apple's supply chain Jenny Chan -- 9. Transparent companies? Legal research strategies to understand forced labour in global supply chains Andreas Ru?hmkorf -- 10. The role of discourse analysis in researching severe labour exploitation Robert Caruana -- 11. Archival trouble : researching sex trafficking in early twentieth-century America Jessica R. Pliley.
Recommended by Reglleto Imbong
aIncludes bibliographical references (pages 194-199) and index.
Keywords: Forced labor -- Research -- Methodology; Human trafficking -- Research -- Methodology; Slavery -- Research -- Methodology; Zwangsarbeit; Forschung; Wissenschaft; Menschenhandel